A Case of a Large Intraabdominal Abscess in a Patient with Cirrhosis Misdiagnosed as Spontaneous Bacterial Peritonitis. (5th October 2022) - Ali, Saeed; Sohail, Abdullah; Brown, Kyle
Abstract : Spontaneous bacterial peritonitis is a known complication of patients with decompensated cirrhosis and ascites. It is differentiated from secondary bacterial peritonitis by the absence of an intraabdominal source of infection. We present a 56-year-old man with alcoholic cirrhosis who underwent multiple paracenteses that yielded fluid with progressively increasing neutrophil counts and several different organisms, recurring despite numerous treatments for SBP. Eventually, a computed tomography (CT) of the abdomen and the pelvis revealed a large intraabdominal abscess (22 × 13 cm) treated with an ultrasound-guided drain and IV antibiotics. Recurrent episodes of SBP despite appropriate antibiotics should raise suspicion for secondary bacterial peritonitis. It is crucial to differentiate SBP from secondary bacterial peritonitis as the mortality of the latter is much higher without prompt treatment. Appropriate antibiotic regimens, prompt surgical treatment, and postoperative care are crucial to improving clinical outcomes in these patients.